2021
DOI: 10.1155/2021/9385917
|View full text |Cite
|
Sign up to set email alerts
|

Submicron SiO2 Powder: Characterization and Effects on Properties of Cement‐Free Iron Ditch Castables

Abstract: Submicron materials are those with particle size diameters between 0.1 and 1 μm. Submicron SiO2 generally refers to SiO2 powder with a D90 < 1 μm (D90 refers to the particle size distribution exhibited by the sample and corresponds, in this case, to 90% of the particles not exceeding a diameter of 1 μm). In this study, a new type of cement-free iron ditch castable was prepared using dense corundum and silicon carbide as the primary raw materials with submicron SiO2 powder as the binder. The effects of submi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
(18 reference statements)
0
0
0
Order By: Relevance
“…As for the second aspect, the addition of metal powders can not only improve the oxidation resistance of ASC castables, but also enhance its explosion resistance. Its anti-explosion mechanism is that the addition of metal powders increases the open pores or/and microcracks inside the ASC, which makes the steam in the ASC easily escape.However, previous studies have shown that adding metal powders can reduce the strength of castable although it has a good explosion resistance effect [22]. Therefore, in practical applications, the amount of metal powders added to ASC castables must be controlled to a very small level.…”
Section: Introductionmentioning
confidence: 99%
“…As for the second aspect, the addition of metal powders can not only improve the oxidation resistance of ASC castables, but also enhance its explosion resistance. Its anti-explosion mechanism is that the addition of metal powders increases the open pores or/and microcracks inside the ASC, which makes the steam in the ASC easily escape.However, previous studies have shown that adding metal powders can reduce the strength of castable although it has a good explosion resistance effect [22]. Therefore, in practical applications, the amount of metal powders added to ASC castables must be controlled to a very small level.…”
Section: Introductionmentioning
confidence: 99%